Late Onset Atypical Pantothenate-Kinase-Associated Neurodegeneration. (24th March 2013) - Diaz, Natalie
Abstract : Introduction . Pantothenate-kinase-associated neurodegeneration (PKAN) is a rare genetic disease and a form of neurodegeneration with brain iron accumulation (NBIA). It most commonly begins in the first two decades of life but should be considered in the differential diagnosis of patients at any age with an atypical progressive extrapyramidal disorder and cognitive impairment. Few late-adult cases have been reported. Case Report . A 50-year-old woman presented with a history of progressive dysarthria and dysphagia secondary to orolingual dystonia. Initial work-up was normal. There was no family history. Her initial symptoms were followed by the onset of blepharospasm, cervical dystonia, Parkinsonism, and cognitive impairment. Follow-up MRI four years after presentation revealed the diagnostic "eye-of-the-tiger" sign. Genetic testing confirmed a homozygous missense mutation consistent with the diagnosis of PKAN. Conclusion . Although PKAN is a rare genetic disorder most commonly seen in childhood, it should be considered in adult patients with a history of progressive focal dystonia or atypical Parkinsonism. As the radiographic findings are quite characteristic, genetic testing should be performed if the MRI shows evidence of iron accumulation. Optimal treatment strategies are not known, and at the current time therapies should be directed at the specific manifestations of the disease.